Analysis of the (non-)functioning American banking system in the 1920s - Soročinová, Viktória; Johnson, Zdenka, 1983-; Chalupecký, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
This master thesis deals with (non-)functioning of the American banking system in the 1920s. Moreover, this thesis tries to put the historical events into broader economic context and follows the causes, which led to the Great Depression in the end of the decade. In the first stage, I will focus on the events, which were taking place in American banking system during the period of the Roaring Twenties. Then, I will focus on the Federal Reserve System’s monetary policy during the examined decade. Afterwards, the key part of my master thesis will be devoted to the analysis of the American banking sector in respect to the agricultural sector and stock market. The main hypothesis, which claims that the American banking system was not functioning during the Golden Twenties, was verified and the result could be seen on the number of bank failures in the United States, lack of regulations from the side of the authorities, or overbanking issue. Furthermore, the main importance of this master thesis is to analyse several factors from different sectors, which had a serious impact on the events in the end of the examined decade and due to the non-functioning American banking system, they harmed millions of American families.
Vedoucí práce: Zdenka Johnson
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses